PERBANDINGAN KEMAMPUAN MIGRASI ADIPOSE-DERIVE STEM CELLS ASAL MANUSIA PADA BERBAGAI MEDIUM PERTUMBUHAN - Rosadi, Imam; Karina, Karina; Rosliana, Iis; Widyastuti, Tias; Wahyuningsih, Komang A; Sobariah, Siti; Afini, Irsyah (Universitas Muhammadiyah Surakarta, 2020)
Cell migration is natural process that plays an important role in development of organisms. Stem cells are an important in the cells migration process due to repairing tissues or organs. Stem cells ability studies towards cell migration process have been developed and studied. In this study, adipose-derived stem cells (ADSCs) were used as cell models of stem cell migration which cultured on medium containing 10% fetal bovine serum (FBS), a combination of 1 0% FBS and L-ascorbic acid (LAA), 10% human platelet-rich plasma (PRP) and 0.1% FBS as a control. The technique that used to analyse cell migration process is scratch assay method. The results of this study indicate that ADSCs were able to migrate on medium containing 10% FBS, 10% FBS-LAA and PRP. On 24 h of observation, the scratched area of ADSCs were 0.70x (control), 0.13x (10% FBS), 0.04x (10% FBS-LAA), and 0.21x (10% PRP) compared to 0 h (1.00x). The width of scratches area in the control group at 24 h was significantly higher than the other treatment groups. This is suggested due to the lack of growth factor contained in the medium as a nutrition for the cells. Therefore, it can be concluded that ADSCs are able to migrate on various medium supplemented by FBS or human PRP.